MORPHOLOGICAL VARIATION IN Eonycteris spelaea (CHIROPTERA: PTEROPODIDAE) FROM THE GREATER AND LESSER SUNDAS ISLANDS, INDONESIA AND DESCRIPTION OF A NEW SUBSPECIES - MAHARADATUNKAMSI MAHARADATUNKAMSI; D. J. KITCHENER (BRIN Publishing (Penerbit BRIN), 1997)
Morphological variation in the cave fruit bat, Eonycteris spelaea from Indonesia and the Philippines was examined using both univariate and multivariate statistical analyses based on measurements of 22 skull characters and 15 external body characters from 270 adult specimens. Other non-meristic characters were also examined. Multiple regression analyses indicated strong sexual dimorphism in both skull and external body characters. Almost all measured characters differed significantly between islands. Thirteen of the 37 characters were also influenced t:he age of adults. Four distinct morphological groups of E. spelaea.were recognised using discriminant function analysis following the removal of the effects of,age and sex on the measurements considered. These were: Jawa/Sumatera Group, Lesser Sunda/Philippines Group, Sulawesi Group and Kalimantan Group. These morphological groups were considered subspecifically distinct; the Kalimantan Group is herein described as a new subspecies.